PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP KEBIJAKAN DEVIDEN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING - Tyasa Putri Paramastri; Yuyun Ristianawati (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study is to determine the effect of Profitability and Liquidity on Dividend Policy with Company Size as a moderating variable in Companies listed on the Indonesian Stock Exchange which are listed in LQ45 in 2018-2022. To test this, researchers used quantitative descriptive methods with secondary data collection techniques in the form of annual financial reports. The data analysis techniques used are multiple linear regression and moderated regression analysis. The results of this research show that Profitability has a significant positive effect on Dividend Policy, Liquidity has an insignificant negative effect on Dividend Policy, Company Size is able to moderate the influence of Profitability on Dividend Policy, Company Size is able to moderate the influence of Liquidity on Dividend Policy.